(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Dryland training is an important component in developing swimming performance, especially to increase the strength and endurance of lower body muscles that contribute to kick speed in freestyle. This study aims to analyze the effect of stair climbing training as a form of dryland training on freestyle kick speed in non-athlete students. The research method used was a quasi-experimental with a one group pretest-posttest design . The subjects of the study consisted of 20 male non-athlete students aged 18–22 years, who were selected using a purposive sampling technique. The intervention was carried out for six weeks with a frequency of three times per week, consisting of 4–6 sets of stair climbing for 30 minutes each session. Swimming kick speed was measured with a stopwatch in a 15-meter track with a streamline position using a footboard. Data were analyzed using a paired t-test to see the difference before and after training. The results showed a significant increase in kick speed (p <0.05) after following the dryland training program. The average travel time decreased from 18.4 seconds to 16.7 seconds. These results indicate that stair climbing provides dynamic force transfer to the major muscles involved in the swimming kick, such as the quadriceps and gluteus muscles. In conclusion, stair climbing is an effective dryland training method to improve freestyle kick performance in non-athlete college students.